Reliability Analysis of Repairable System: Screw Press Machines - Nofirman Firdaus (ITP Press)
In this paper, Reliability analysis is performed on screw press machines. The analysis starts with system reliability based on ten components and one-year failure data. To identify which component has a negative impact on system reliability and to what degree the impact is, reliabiity importance indices are performed based on Birnbaum and operational criticality index (OCI). By identifying the rank of component importances, maintenance could focus on the critical parts, and then improve system reliability. In addition, maintenance optimization for inspection and replacement schedule are also presented in this paper.